Ziarah Kubur Pada Masyarakat Desa Muara Musu Kecamatan Rambah Hilir Kabupaten Rokan Hulu - Sinta Rahmayeni; Salmaini Yeli (Journal Hub for Humanities and Social Science, 2024)
This research aimed at describing grave pilgrimage that hasbecome a tradition for most communities in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency.Grave pilgrimage was the community activities to visit private or public cemeteries that wereimplemented individually or in groups.  The communities pray for relatives or family members who died to be given spaciousness in their graves and given a proper positionby Allah SWT.  The problems of this research were: first, how were the ethics and procedures for implementing the grave pilgrimage ?, second, what were the values existing in the grave pilgrimage activities implemented by the community in Muara Musu Village, Rambah Hilir District, Rokan Hulu Regency ?.  It was a field research: a study that did not use calculated data.This research used a qualitative approach that was directed to provide facts or events systematically and accurately.  Interview, documentation, and observation methods were used for collecting the data.  Data analysis was the decomposition of data to produce deductive and inductive conclusions.  The findings of this research showed that in the grave pilgrimageinMuara Musu village has uniqueness, lime water was one of the procedures in the grave pilgrimagethat must be brought with  when going to pilgrimage, it has purpose to pour the grave to be cold.  Pilgrimage activities were implemented on certain days, for example on Fridays,the end of Ramadhanmonth and before Idul Fitri.Their penchant inimplementing grave pilgrimagewas related to the phenomenon of learning religion through Sulukin the village. Because, they got good teaching and contained good elements for the community.  Besides, the grave pilgrimage has also motivation and good values aiming to remind everyone about the death, so that his life would be better that can trainhim to accept and be patient in facing every obstacle or testcoming from Allah SWT.